A suprasellar subarachnoid pouch; aetiological considerations. Issue 10 (October 1984) - Binitie, O; Williams, B; Case, C P
Abstract : A child with hydrocephalus treated by a valved shunt was reinvestigated after developing a shunt infection. A pouch was discovered invaginating the floor of the third ventricle and filling slowly with CSF from the region of the interpeduncular cistern. Histology and mechanisms of this pouch formation are discussed.